(untitled) (Student’s Journal of Health Research Africa, 2025)
Background Impaired glucose tolerance or impaired fasting glucose are hallmarks of prediabetes, a crucial transitional stage that frequently precedes Type 2 Diabetes Mellitus (T2DM). There is growing evidence that glucose homeostasis is significantly impacted by deficiencies in micronutrients, especially vitamin D (25-hydroxyvitamin D). In India, vitamin D insufficiency is still common despite the country’s abundant sunshine. Objective In a prediabetic cohort in Keonjhar, Odisha, this study attempts to assess the relationship between serum vitamin D levels, insulin resistance (HOMA-IR), and glycemic variability. Methods Over the course of a year, a retrospective observational study was carried out at a tertiary medical facility in Keonjhar. 250 participants with prediabetes (HbA1c 5.7–6.4%) between the ages of 30 and 60 were enrolled in the study. Medical records were consulted for information on anthropometry, fasting plasma glucose (FPG), post-prandial glucose (PPG), HbA1c, fasting insulin, and serum 25(OH)D. The Homeostatic Model Assessment (HOMA-IR) was used to calculate insulin resistance. The standard deviation of FPG (SD-FPG) over the follow-up period was used to measure glycemic variability (GV). Results Widespread insufficiency was shown by the mean blood vitamin D level of . Vitamin D levels and HOMA-IR showed a significant inverse connection Additionally, glycemic variability (SD-FPG) was considerably higher in patients with severe vitamin D insufficiency () than in those with sufficient levels (). Conclusion In prediabetic individuals in Keonjhar, vitamin D deficiency is substantially linked to increased insulin resistance and unstable glycemic control. In this area, treating hypovitaminosis D may be a good way to postpone the onset of type 2 diabetes. Recommendation Given the significant frequency of vitamin D insufficiency and its correlation with metabolic dysregulation in prediabetes, including vitamin D status assessment into standard prediabetes screening techniques may provide a cost-effective means for early metabolic risk stratification. Additional prospective studies are necessary.